Kajian metode pengasaman dalam proses produksi minyak kelapa ditinjau dari mutu produk dan komposisi asam amino blondo - Susanto, Tri (Balai Riset dan Standardisasi Industri Palembang, 2012)
The study of acidification method in the coconut oil production has been conducted as an alternative production process. Coconut oil products produced compared with the quality requirements of SNI 01-2902-2011 and amino acid composition test done on the product side (blondo) using HPLC to detect the failure of the production through the acidification process. The yield of palm oil produced through a acidification process ranged from 14 to 32.3%, while the coconut oil quality includes the water content ranged from 0.1 to 0.48%, impurities ranged from 0.01 to 0.06%, number iodide ranged from 6.8 to 9.8%, the levels of free fatty acids (FFA) ranged from 0.2 to 1.26, saponification number 243-267, color and aroma were clear, while the protein content was calculated as total N-Kjeldhal ranged from 9.09 to 21.8%. Blondo (by products) were analyzed using HPLC, the results of the chromatogram peaks showed some amino acids such as aspartic acid, glutamine, serine, histidine, glycine, argini, alanine, tyrosine, methionine, valine, phenylalanine, isoleucine, leucine, and lysine. In the failure of acidification process indicates that it does not appear the leucine and lysine peaks in chromatogram, physical properties indicate a rancid smell and color of unclear on samples of coconut oil. The results showed that the method of acidification using acetic acid (CH3COOH) can be used as a method for the coconut oil production that meets the quality requirements of SNI 01-2902-2011 and APCC Standards Asian and Pacific Coconut Community, 2006.Keywords : Acid composition, acidification, blondo amino, coconut oil, HPLC, SNI 01-2902-2011AbstrakTelah dipelajari metode pengasaman sebagai alternatif proses produksi minyak kelapa. Produknya dibandingkan dengan syarat mutu SNI 01-2902-2011 dan dilakukan uji komposisi asam amino pada produk samping (blondo) menggunakan HPLC untuk mendeteksi kegagalan proses. Rendemen minyak kelapa yang diproduksi antara 14- 32,3%, sedangkan kualitas mutu minyak kelapa meliputi kadar air 0,1-0,48%, kadar kotoran 0,01-0,06%, bilangan iodida 6,8-9,8%, kadar asam lemak bebas (FFA) 0,2-1,26, bilangan penyabunan 243-267, warna jernih dan aroma khas, dan kadar protein dihitung sebagai total N-Kjeldhal 9,09-21,8%. Produk samping blondo dianalisa menggunakan HPLC, kromatogram blondo menunjukkan puncak asam amino asam aspartat, glutamin, serin, histidin, glisin, arginin, alanin, tirosin, metionin, valin, fenilalanin, isoleusin, leusin dan lisin. Pada proses produksi yang gagal tidak muncul puncak kromatogram leusin dan lisin, sifat fisiknya menunjukkan bau tengik dan warna keruh pada sampel tersebut. Metode pengasaman menggunakan asam asetat (CH3COOH) dapat dijadikan sebagai metode proses produksi minyak kelapa yang memenuhi persyaratan mutu SNI 01-2902- 2011 dan APCC Standards Asian & Pacific Coconut Community 2006.Kata kunci : HPLC, komposisi asam amino blondo, minyak kelapa, pengasaman, SNI 01-2902-2011